From defense to offense: antimicrobial peptides as promising therapeutics for cancer - Zare-Zardini, Hadi; Saberian, Elham; Jenča, Andrej; Ghanipour-Meybodi, Razieh; Jenča, Andrej; Petrášová, Adriána; Jenčová, Janka (Frontiers in Oncology, 2024)
Antimicrobial peptides (AMPs), naturally occurring components of innate immunity, are emerging as a promising new class of anticancer agents. This review explores the potential of AMPs as a novel class of anticancer agents. AMPs, naturally occurring peptides with broad-spectrum antimicrobial activity, exhibit several characteristics that make them attractive candidates for cancer therapy, including selectivity for cancer cells, broad-spectrum activity, and immunomodulatory effects. Analysis of a dataset of AMPs with anticancer activity reveals that their effectiveness is influenced by various structural properties, including net charge, length, Boman index, and hydrophobicity. These properties contribute to their ability to target and disrupt cancer cell membranes, interfere with intracellular processes, and modulate the immune response. The review highlights the promising potential of AMPs as a new frontier in cancer treatment, offering hope for more effective and less toxic therapies. AMPs demonstrate promising potential in cancer therapy through multiple mechanisms, including direct cytotoxicity, immune response modulation, and targeting of the tumor microenvironment, as evidenced by extensive preclinical studies in animal models showing tumor regression, metastasis inhibition, and improved survival rates. AMPs show significant potential as cancer therapeutics through their direct cytotoxicity, immune response modulation, and tumor microenvironment targeting, with promising results from preclinical studies and early-phase clinical trials. Future research should focus on optimizing AMP properties, developing novel delivery strategies, and exploring synergistic combination therapies to fully realize their potential as effective cancer treatments, while addressing challenges related to stability, delivery, and potential toxicity.